Dynamic linkages between woman labor participation and economic growth in ASEAN - Muttaqin, Ecky Imamul; Widyasari, Maya; Aulia, Sulthonul; Adzimatinur, Fauziyah; Cheong, Jia Qi (Jurnal Ekonomi & Studi Pembangunan, 2026)
This study analyses the dynamic interplay between women's labor market attributes and economic growth in Southeast Asia, specifically in Indonesia, Thailand, Malaysia, and Singapore, from 2000 to 2023. This study, inspired by modernisation theory and ongoing gender inequalities in labor markets, examines the interplay between female vulnerable employment, female self-employment, and the female-to-male labor force participation ratio in relation to GDP growth. A Panel Vector Autoregression (PVAR) model, estimated via the Generalised Method of Moments (GMM), utilises data from the World Development Indicators to identify bidirectional and dynamic causal links among the variables. The estimation results indicate that female vulnerable employment and female self-employment positively and significantly influence GDP growth, while the female-to-male labor force participation ratio demonstrates a negative but statistically negligible effect. Impulse response functions indicate that shocks to female self-employment have a positive impact on GDP in the short term, but shocks to female vulnerable employment first decrease GDP before stabilising. Forecast error variance decomposition reveals that GDP fluctuations are predominantly influenced by their own shocks, but female self-employment progressively contributes to GDP variance with time. The findings underscore the significant yet diverse impact of women's labor patterns on economic growth, highlighting the necessity for measures that mitigate vulnerability and enhance the quality of female work in ASEAN countries.